Flipped classroom: Challenges and benefits of using social media in English language teaching and learning - Han, Shujun (Frontiers in Psychology, 2022)
Due to the emergence of new technologies, reforms in higher education require changes in traditional education. The flipped classroom approach can be a solution to such educational changes to create a student-centered individual learning environment. This approach, which is a type of blended learning, has effectively integrated traditional education and social networks using both environments inside and outside the classroom. The current review is to provide an overview of flipped classroom studies in language teaching contexts. Particularly, the study put emphasis on revealing and addressing the potential benefits and challenges of flipped classroom approach for teaching using social media. It focused on learning environments that students were exposed to the lecture content before the class in a collaborative and interactive learning environment using well-known social media applications. Twenty five journal publications of flipped classrooms were analyzed in terms of their flipped learning activities, learner achievement, learner attitude, and challenges encountered. The analysis of the selected studies showed that the flipped classroom approach has a positive effect on learning, reducing cognitive load, involvement, accuracy, motivation, attitude, and satisfaction with the course and self-efficacy in higher education, and one of the most important challenges of the flipped classroom is the lack of familiarity and appropriate adaptation of students. With the inversion method, there was an increase in teachers’ workload. According to the analysis of the selected research findings, it is concluded that higher education can effectively use this method.